Load cell-based measurement of compression spring constants in series and parallel configurations - Meri Rahmi; Yuliar Yasin Erlangga; Aida Mahmudah; Rofan Yulian Romansyah (Jurnal Polimesin, 2026)
Selecting appropriate springs is a critical factor in press tool construction, as incorrect selection compromises performance, safety, and production efficiency. This study investigates the elastic behavior of Misumi standard compression springs by measuring force and spring constant using a 100 kg-capacity load cell integrated into a custom spring tester. Experiments were conducted on four spring types (SWF, SWL, SWM, SWH) in single, series, and parallel configurations. This study experimentally investigates the elastic behavior of Misumi standard compression springs bymeasuring force and spring constant using a 100 kg-capacity load cell integrated into a custom spring tester. Results show that the parallel configuration increases the total spring constant proportionally with the number of springs (e.g., four SWF-60-100 springs in parallel yield a combined reaction force of 27.1 kg/10 mm, approximately 4.2 times the single-spring value of 6.4 kg/10 mm), while the series configuration reduces the constant due to the greater cumulative deflection. The load cell method demonstrated superior accuracy over manual methods, with spring-length deviations from Misumi catalog values ranging from 0% to 4.8%, confirming consistency with manufacturing tolerances. Spring constant values computed from load cell readings deviated by less than 5% from values estimated using Hooke's law. This study provides quantitative evidence supporting the use of load-cell-based testing in spring selection for press tool applications.